ANALISIS KONFLIK PERAN GANDA DAN TINGKAT STRES KERJA TERHADAP KINERJA KARYAWAN WANITA - Rini Aristiani Safitri; Ardianti Agustin (PSIKOWIPA (Psikologi Wijaya Putra), 2023)
Women have a dual role as wives and mothers in the household, but many also work. This condition causes women to face multiple roles and work stress that affects their performance. This study aims to examine the effect of multiple role conflict and work stress on the performance of female employees at CV. Electric Steel Light. The research subjects consisted of 84 married female employees, selected by purposive sampling method. Data is collected through a questionnaire that measures multiple role conflict, job stress, and work performance. Data analysis used multiple linear regression with the help of the SPSS for Windows 16.0 program. The results showed that the p-value = 0.000 <0.05, which indicates a significant influence between multiple role conflict and work stress on the performance of female employees at CV. Electric Steel Light. The coefficient of determination (R square) of 0.25 indicates that multiple role conflict and stress contribute 25% to work performance, while the remaining 75% is influenced by other factors not examined in this study. Based on calculations, the effective contribution of multiple role conflict to work performance is 8.14%, while the effective contribution of work stress is 16.83%. This shows that work stress has a greater influence than multiple role conflict on the performance of female employees at CV. Electric Steel Light.